2015
DOI: 10.1152/ajpendo.00406.2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the physiological relevance of systemic vs. portal insulin delivery to evaluate whole body glucose flux during an insulin clamp

Abstract: To understand the underlying pathology of metabolic diseases, such as diabetes, an accurate determination of whole body glucose flux needs to be made by a method that maintains key physiological features. One such feature is a positive differential in insulin concentration between the portal venous and systemic arterial circulation (P/S-IG). P/S-IG during the determination of the relative contribution of liver and extra-liver tissues/organs to whole body glucose flux during an insulin clamp with either systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 94 publications
0
44
0
2
Order By: Relevance
“…In contrast, fed rodents and fasted large animals respond to insulin by rapidly suppressing glycogenolysis (2,(7)(8)(9). In addition, Perry et al infused insulin into a peripheral vein at a rate (3 mU/kg/min) that has been shown to increase arterial levels 3-fold (17,18,51), but which would not have elevated insulin at the liver (26). Therefore, that study does not provide insight into the suppression of HGP due to inhibition of lipolysis in the context of an increase in insulin secretion (i.e., a rise in portal vein insulin delivery).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, fed rodents and fasted large animals respond to insulin by rapidly suppressing glycogenolysis (2,(7)(8)(9). In addition, Perry et al infused insulin into a peripheral vein at a rate (3 mU/kg/min) that has been shown to increase arterial levels 3-fold (17,18,51), but which would not have elevated insulin at the liver (26). Therefore, that study does not provide insight into the suppression of HGP due to inhibition of lipolysis in the context of an increase in insulin secretion (i.e., a rise in portal vein insulin delivery).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the route of insulin delivery can have a major impact on both the overall response of the liver and the mechanisms by which that response is achieved. Indeed, over a range of insulin doses, peripheral insulin infusion was not as effective at suppressing HGP as compared with direct infusion into the portal vein (26).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Liver hypoinsulinemia was reported in studies on rats, where it was shown that when arterial INS levels were clamped at twofold above basal levels during peripheral INS infusion, the portal vein INS concentration was still marked as "deficient," or below the basal level. 13 Peripheral IR mediated degradation and the short plasma T 1/2 (5 min) of INS may presumably attribute to observations in those early studies, which showed that only 1% of exogenous INS was delivered to the liver. 14 Therefore, in order to obtain sufficient INS concentrations in the liver, peripheral hyperinsulinemia is necessary.…”
mentioning
confidence: 86%